2021
DOI: 10.15326/jcopdf.2021.0245
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Patients with COPD Hospitalized for Coronavirus Disease 2019

Abstract: For personal use only. Permission required for all other uses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…For instance, the COPD group was older than the non-COPD group. This finding has been previously reported [ 10 , 40 ], and could be related to older patients with COPD delaying seeking medical help or more comorbidities and severe COPD exacerbations not manageable at home than younger patients [ 41 ]. In order to address the differences among groups, we leveraged multifactor adjustment, which included age in all logistic regression models tested and comorbid diseases in Models 2 and 3.…”
Section: Discussionsupporting
confidence: 78%
“…For instance, the COPD group was older than the non-COPD group. This finding has been previously reported [ 10 , 40 ], and could be related to older patients with COPD delaying seeking medical help or more comorbidities and severe COPD exacerbations not manageable at home than younger patients [ 41 ]. In order to address the differences among groups, we leveraged multifactor adjustment, which included age in all logistic regression models tested and comorbid diseases in Models 2 and 3.…”
Section: Discussionsupporting
confidence: 78%
“…In a meta-analysis of 15 studies, Alqahtani et al report that only 2% of COVID-19 patients have COPD. 41,42 Multiple studies from the Veterans Affairs (VA) reported a drop in COPD exacerbations during the pandemic, which could reflect masking and social distancing behaviors during the pandemic that prevented infections in this potentially vulnerable population. 43,44 Baum et al reported a 48.4% total reduction in admissions with a principal diagnosis of COPD to the VA in the first 4 months of the pandemic.…”
Section: Covid-19 Diagnosismentioning
confidence: 99%
“…A meta-analysis stated that a previous history of COPD increases the risk of severe COVID-19 4-fold, and active smoking increases the risk of severe COVID-19 (31). COPD has been associated with a higher need for intensive care, invasive ventilation, and a higher risk of death in patients with COVID-19 (32,33). Patients with COPD presenting with new or increased respiratory symptoms, fever, or other COVID-19 symptoms should be tested for COVID-19, even if they are mild (34).…”
Section: Copdmentioning
confidence: 99%